Comparison of Mirena and Liletta levonorgestrel intrauterine devices for the treatment of endometrial intraepithelial neoplasia and grade 1 endometrioid endometrial cancer - Chaudhari, Sonal R.; Lai, Tiffany S.; Zakhour, Mae; Myung Shin, Sim; Baltayan, Armine; Tan, Hongying; Cohen, Joshua G. (Gynecologic oncology reports, 2023)
•Liletta IUD is noninferior to Mirena IUD for regression of EIN or low-risk endometrial cancer after 3 and 6 months.•Liletta IUD is noninferior to Mirena IUD for regression of EIN after 3, 6, and 9 months.•Liletta IUD has reasonable efficacy as a single-agent therapy for EIN or low-risk endometrial cancer.•Liletta IUD was more commonly used for treatment of EIN at a safety net hospital than at an academic center. Current standard nonsurgical management of endometrial intraepithelial neoplasia (EIN) and grade 1 endometrioid endometrial cancer (g1EEC) is the Mirena levonorgestrel intrauterine device (M−IUD). This retrospective study was designed primarily to determine noninferiority of the Liletta IUD (L-IUD) for pathologic regression of EIN and g1EEC compared to the M−IUD at 6 months of continuous use. Secondary objectives include to determine noninferiority as above at 3, 9, and 12 months of continuous use and to identify factors including DNA mismatch repair (MMR) status associated with pathologic regression after LNG-IUD use. A retrospective observational study was performed with patients treated for EIN or g1EEC and managed continuously with M- or L-IUD. Patients with recent (within 6 months) or concurrent progesterone use were excluded. For the EIN group, the noninferiority margin of odds ratio was predetermined to be 0.58, and for the g1EEC group it was 0.64. 62 patients from an academic center and a safety-net hospital were identified with continuous M−IUD (n = 44) or L-IUD (n = 18) use for EIN or g1EEC. 85% of patients treated with L-IUD were from a safety-net hospital, which had 63% with public insurance. At 3/6/9 months, 54/71/73% of patients with M−IUD and 80/83/100% with L-IUD had pathologic regression of EIN (95% confidence interval of estimated odds ratio 1.00–2.07/0.84–2.03/0.69–2.10). Lifetime smoking status, not MMR status, was significantly associated with pathologic regression. L-IUD is an effective fertility-sparing treatment for EIN. L-IUD is noninferior to M−IUD for pathologic regression of EIN after 3,6, and 9 months. Further larger studies are warranted to validate findings in EIN and g1EEC.